Measuring Enterprise Resource Planning (ERP) Systems Effectiveness in Indonesia - Adhi Wibowo; Marti Widya Sari (Universitas Ahmad Dahlan, 2018)
Refining DeLone and McLean’s (D&M) information system model and technology-organisation-environment (TOE) framework, this research identifies the prominent factors that determine ERP system success. Hypotheses are also drawn based on supporting theories to evaluate the causal relationship between the success determinants. The level of achievement is measured by system quality, information quality, service quality, external quality and top management support, which intermediated by perceived usefulness and user satisfaction towards business benefits. To provide empirical evidence, 86 valid samples out of 156 were collected using a web survey that targeted ERP users in Indonesia. Furthermore, Partial Least Squares–Structural Equation Modelling (PLS-SEM) algorithm were applied to check the proposed hypotheses. The results suggest system quality, information quality and service quality significantly affect user satisfaction, whereas they moderately impact on perceived usefulness. Interestingly, external pressures were reported as being the biggest influence on user satisfaction and positively impacted on perceived usefulness. Despite being fairly predictive to perceived usefulness, top management support along with general perceptual factors ultimately promote system success by elevating business benefits.